Neuromyelitis Optica (NMO) in Children: A Rare Case Report - Dodik Tugasworo; Aditya Kurnianto; Retnaningsih Retnaningsih; Yovita Andhitara; Rahmi Ardhini; Tomy Nugroho; Jethro Budiman (Faculty of Medicine, Diponegoro University, 2020)
Background: Neuromyelitis optica (NMO) is a rare autoimmune disease that covers 20-30% of diseases related to autoimmune disorders and about 1% of demyelination diseases. NMO symptoms are vary between individuals, there are generally 2 main symptoms, transverse myelitis and optic neuritis. This article reported a child with NMO disease based on The Consensus of the International Panel for NMO Diagnosis (IPND) 2015.Case Presentation: An 8-year old boy with spastic tetraparesis, bilateral nervus opticus dysfunction, urinary retention, and allodynia et causa suspected NMO. Patient received therapy using high-dose intravenous methylprednisolone and showing a clinical improvement.Conclusion: This patient was diagnosed NMO based on IPND 2015 with an unknown AQP4-Ab status accompanied by supporting clinical symptoms. The management of NMO with high-dose intravenous methylprednisolone in this patient provides a meaningful response to the clinical improvement of the disease.